Rates of severe complications in patients undergoing colorectal surgery for deep endometriosis—a retrospective multicenter observational study. (12th July 2022) - Hudelist, Gernot; Korell, Matthias; Burkhardt, Michael; Chvatal, Radek; Darici, Ezgi; Dimitrova, Desislava; Drahonovsky, Jan; Haj Hamoud, Bashar; Hornung, Daniela; Krämer, Bernhard; Noe, Guenter; Oppelt, Peter; et al.
Abstract: Introduction: Surgical experience and hospital procedure volumes have been associated with the risk of severe complications in expert centers for endometriosis in France. However, little is known about other certified units in Central European countries. Material and methods: This retrospective observational study included 937 women who underwent surgery for colorectal endometriosis between January 2018 and January 2020 in 19 participating expert centers for endometriosis. All women underwent complete excision of colorectal endometriosis by rectal shaving, discoid or segmental resection. Postoperative severe complications were defined as grades III–IV of the Clavien–Dindo classification system including anastomotic leakage, fistula, pelvic abscess and hematoma. Surgical outcomes of centers performing less than 40 (group 1), 40–59 (group 2) and ≥60 procedures (group 3) over a period of 2 years were compared. Results: The overall complication rate of grade III and IV complications was 5.1% (48/937), with rates of anastomotic leakage, fistula formation, abscess and hemorrhage in segmental resection, discoid resection and rectal shaving, respectively, as follows: anastomotic leakage 3.6% (14/387), 1.4% (3/222), 0.6% (2/328); fistula formation 1.6% (6/387), 0.5% (1/222), 0.9%; (3/328); abscess 0.5% (2/387), 0% (0/222) and 0.6% (2/328); hemorrhage 2.1% (8/387), 0.9% (2/222) and 1.5% (5/328). Higher overall complication rates were observed for segmental resection (30/387, 7.8%) than for discoid (6/222, 2.7%, P = 0.015) or shaving procedures (12/328, 3.7%, P = 0.089). No significant correlation was observed between the number of procedures performed and overall complication rates ( r Spearman = −0.115; P = 0.639) with a high variability of complications in low‐volume centers (group 1) . However, an intergroup comparison revealed a significantly lower overall severe complication rate in group 3 than in group 2 (2.9% vs 6.9%; P = 0.017) without significant differences between other groups. Conclusions: A high variability in complication rates does exist in centers with a low volume of activity. Major complications may decrease with an increase in the volume of activity but this effect cannot be generally applied to all institutions and settings.